What Are Motivations Behind Entrepreneurship Intention and Behavior Among Postgrads in Zhejiang, China? - Qian, Yi (Scholar: Human Sciences, 2024)
Purpose: Entrepreneurship plays a significant role in recovering and boosting development and innovation in the economy. This study aims to investigate the factors that impact master’s degree students’ entrepreneurship intention and behavior in three cities: Hangzhou, Ningbo, and Wenzhou, Zhejiang Province, China. Attitude toward being an entrepreneur, subject norms for being an entrepreneur, entrepreneurial training & development, entrepreneurship education, entrepreneurial motivation, entrepreneurial intention, and entrepreneurship behavior are proposed the causal relationship for the conceptual framework. Research design, data, and methodology: The researcher applied the quantitative method (n=500), using online questionnaire. This research applied judgmental, quota and convenience sampling method to collect the data. The research used Structural Equation and Model and Confirmatory Factor Analysis to analyze the data, which include reliability, construct validity, and model fit. Results: The result of this study demonstrate that attitude toward being an entrepreneurial intention, subject norms for being an entrepreneur, entrepreneurial training & development, entrepreneurship education, entrepreneurship motivation, and entrepreneurial intention significantly impact college students’ entrepreneurship behavior. Conclusion: This study suggested that training and education are significant to master’s degree students to understand the importance of entrepreneurship, which helps to encourage more students to choose to start their businesses.